Is it necessary to discontinue metformin in diabetic patients with GFR > 60 ml/min per 1.73 m2 undergoing coronary angiography: A controversy still exists? - Namazi, Mohammad Hasan; AlipourParsa, Saeed; Roohigilani, Kobra; Safi, Morteza; Vakili, Hossein; Khaheshi, Isa; Abdi, Fatemeh; Zare, Adel; Esmaeeli, Shooka (Acta Biomedica Atenei Parmensis, 2018)
Background: Although metformin is not directly nephrotoxic, it has been postulated that it can impair gluconeogenesis from lactate, which may lead lactate to be accumulated under circumstances such as contrast-induced nephropathy. The present study aims to assess the role of metformin in lactate production in a group of diabetic patients with GFR > 60 ml/min per 1.73 m2undergoing coronary angiography. Methods: In the present randomized clinical trial, 162 metformin-treated diabetic patients were enrolled. The enlisted patients were scheduled to undergo coronary angiography at Modarres Hospital from Feb 2012 to Nov 2012. Patients were randomly allocated to continue metformin during peri-angiography period (M (+) group) or to stop the medication 24 hours prior the procedure (M (-) group). All the patients had glomerular filtration rate of >60 mL/min per 1.73 m2. Iodixanol was the only contrast media which in all patients. Metformin-associated lactic acidosis (MALA) was defined as an arterial pH 5 mmol⁄L. Results: 162 patients, including79 (48.7%) male and 83 (51.3%) female patients were enrolled in the study. The average of GFR was comparable in both groups (76 ml/min per 1.73 m2 in the M (+) group versus 79 ml/min per 1.73 m2 in the M (-) group, p=0.53). No significant difference was observed in the mean dose of metformin before the study between the 2 groups (2.18 tablets per day in M (+) group vs. 2.21 tablets per day in M(-) group, p=0.62).No lactic acidosis was observed in the studied groups. Conclusion: In conclusion, the results of the present study indicate that metformin continuation in diabetic patients with a GFR of more than 60 ml/min per 1.73 m2 undergoing coronary angiography does not enhance the risk of MALA development.